PENGARUH KEPEMIMPINAN, MOTIVASI, DAN DISIPLIN TERHADAP KINERJA ANGGOTA POLRES PEKALONGAN - Muhammad Rizzal Setiaji, 11.05.51.0053 (Students Journal of Economic and Management, 2015)
This study analyzed the effect of Leadership , Motivation , and Discipline in Performance of the members . Object of study in this paper is Pekalongan Police. The sampling technique in this research is using purposive sampling of 100 respondents in the sample data collection method using a questionnaire (questionnaire) by distributing a list of questions to the respondent in order to obtain information . The research objective was formulated to determine the effect of leadership , motivation , and Discipline of the performance of members. The data were analyzed using factor analysis to test the validity of the question items , Cronbach alpha formula to test the reliability of the instrument , regression analysis, to examine the influence of each partially independent variables tested by regression analysis . The results of the research are: (1).Leadership has a positive and significant impact on the performance of Members . (2) Motivation has a positive and significant impact on the performance of Members. (3) Discipline has a positive and significant impact on the performance of Members . Keywords : Leadership, Motivation, and Discipline in Performance of the members